2021
DOI: 10.1088/1361-651x/ac2b03
|View full text |Cite
|
Sign up to set email alerts
|

Design of Menger sponge fractal structural NiTi as bone implants

Abstract: Finite element simulations were performed to investigate potential applications of Menger sponge fractal NiTi structures as bone implants. The tunable correlations between porosity and fractal parameters in Menger sponge fractal structures were explored to match the characteristics of the natural bones, including porosity, hierarchical porous structures, and fractal dimensions. The computational results demonstrate that the broad range of elastic modulus and yield stress in our designed fractal NiTi structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Their study demonstrated that the mechanical properties of this material are more similar to those of human long bones, potentially extending the application range of Ni-Ti SMA with graded porosity. Zhang et al [89] employed finite element simulations to evaluate the potential use of Menger sponge fractal Ni-Ti structures as bone implants. Their study showed that by adjusting the porosity and fractal parameters of the structure to match the porosity characteristics of bone, the Menger sponge fractal structure holds great potential for bone implantation.…”
Section: Application Of Ni-ti Porous Structurementioning
confidence: 99%
“…Their study demonstrated that the mechanical properties of this material are more similar to those of human long bones, potentially extending the application range of Ni-Ti SMA with graded porosity. Zhang et al [89] employed finite element simulations to evaluate the potential use of Menger sponge fractal Ni-Ti structures as bone implants. Their study showed that by adjusting the porosity and fractal parameters of the structure to match the porosity characteristics of bone, the Menger sponge fractal structure holds great potential for bone implantation.…”
Section: Application Of Ni-ti Porous Structurementioning
confidence: 99%
“…For porous materials, the design of the porous structure is expected to enable the structural material to obtain new functional properties [33][34][35][36], which implies that the hysteresis loops of the porous SMAs could be modulated through the design of pore distributions. Inspired by atomic crystal structures, we proposed several porous SMA models with simple cubic (SC), body-centered cubic (BCC) and face-centered cubic (FCC) ordered porous distributions with varied porosity ranging from 10% to 40%.…”
Section: Microstructure Design Of Porous Smas To Achieve Narrow Hyste...mentioning
confidence: 99%
“…Its geometric characteristics are irregular porous structure. In the past, people have tried to establish the porous fractal microstructure of cancellous bone [5].…”
Section: Introductionmentioning
confidence: 99%